The effect of guided inquiry learning model on students' critical thinking skills in biology learning - Anggrian El Ritli; Miza Nina Adlini (Master Program of Biology Education, Universitas Lambung Mangkurat, Banjarmasin, Indonesia, 2022)
The quality of education in preparing students to have critical thinking skills has not been optimal. Guided inquiry stimulates the thinking ability of students. This study analyses the guided inquiry learning model's effect on students' critical thinking skills on the body's defence system material. This research is quasi-experimental. The population in this study were four classes with a sample consisting of two classes, namely XI IPA A as the experimental class and XI IPA B as the control class. The sampling technique used random cluster sampling. Data collection techniques using multiple choice questions. The results showed: that the calculation of the paired sample t-test in the guided inquiry learning model got a significant value (sig) of 0.00, which means that the sig value is smaller than 0.05 (0.00<0.05). This result shows a probability of less than 0.05, meaning the guided inquiry learning model between the experimental and control classes is not the same. The pre-test and post-test values are more significant than 0.05 (sig>0.05), so it concluded that the data in this study are homogeneous. There is a significant difference in the use of this learning model that educational institutions should follow up. Teacher qualifications need to be improved in innovating and implementing this learning model to optimize students' critical thinking skills.Abstrak Kualitas pendidikan dalam mempersiapkan peserta didik agar memiliki kemampuan berpikir kritis belum optimal. Inkuiri terbimbing merangsang kamampuan berpikir peserta didik. Penelitian ini bertujuan untuk menganalisis pengaruh model pembelajaran inkuiri terbimbing terhadap kemampuan berpikir kritis siswa pada materi sistem pertahanan tubuh. Penelitian ini adalah eksperimen semu. Populasi dalam penelitian ini adalah empat kelas dengan sampel terdiri atas dua kelas yaitu XI IPA A sebagai kelas eksperimen dan XI IPA B sebagai kelas kontrol. Teknik pengambilan sampel menggunakan cluster random sampling. Teknik pengumpulan data menggunakan soal pilihan berganda. Hasil penelitian menunjukkan: perhitungan paired sampel t test pada model pembelajaran inkuiri terbimbing mendapatkan nilai signifikan (sig) sebesar 0,00 yang artinya nilai sig lebih kecil dari 0,05 (0,00<0,05). Ini menunjukkan probabilitas kurang dari 0,05 yang berarti model pembelajaran inkuiri terbimbing antara kelas eksperimen dan kelas kontrol tidak sama. Nilai pre-test dan post-test lebih besar dari 0,05 (sig>0,05) maka dapat disimpulkan bahwa data dalam penelitian ini bersifat homogen. Adanya perbedaan signifikan dengan penggunaan model pembelajaran ini hendaknya ditindaklanjuti oleh lembaga pendidikan. Kualifikasi guru perlu ditingkatkan dalam melakukan inovasi dan implementasi model pembelajaran ini untuk mengoptimalkan kemampuan berpikir kritis peserta didik.